La planificación estratégica como herramienta de competitividad en la industria láctea de Cotopaxi - Yánez Zapata, Valeria Paulina (2021)
The dairy industry in the Cotopaxi province plays a very important role in the national economy; However, it has not shown itself to be competitive with the dairy industry of the large companies in the regional and national sector; This research project aims to define a strategic management model that, when applied to SMEs in the dairy industry, promotes their competitiveness in the market. The research design is field based with bibliographic support. Among the main results obtained through the 86 dairy SMEs certified by the Ministry of Agriculture and Livestock (MAG), it was obtained that 60% of all industries do not carry out strategic planning and of the 40% that do so, 70% are not Familiar, which is why its incidence on competitiveness is very poor, by virtue of which a strategic planning model is presented that has taken as its fundamental axis the circle of continuous improvement developed by Edward Deming. It is distributed as follows: the Plan considers Phase I through Diagnosis and Phase II through Direction, which is going to be done, we find it in Phase III through the Implementation of the Strategy, for Verification we will use Phase IV in the Evaluation of the Strategy and finally to Act we will apply Phase V in the continuous improvement.